CARACTERIZAÇÃO MINERALÓGICA DE ARGILAS BENTONÍTICAS - Caetano, Elenice Hass (2015)
Clay minerals are hydrated silicates of Aluminum, Iron and Magnesium that has lamellar structure (phyllosilicates) composed by continuous SiO4 tetrahedral layers connected to bi and tri metals hydroxide octahedral layers. The layers are continuous and hexagonally ordered regarding to crystallographic axis a and b. The arrange of clays minerals determines the type of clay mineral as 1:1 or 2:1. The 2:1 clays minerals are divided in groups: Vermiculite, Mica, Chlorite, Saponite, Paligorskita and the Smectite group. Among the Smetectite group stands out the Bentonite, the most abundant clay mineral and that shows 2:1 phyllosilicates structure composed by two silicate tetrahedral layers and one alumina octahedral layers, both connected by oxygen atoms in common. The great technological interest in these clay results of the high cation exchange capacity, swelling by water and low size of crystals. Such properties favor the clays modification to discovery new applications. Thus, the clays minerals are an essential step for the discovery of technological applications as well as the fundamental properties of clays. In this work, were characterized four samples of clays through of X-Ray Diffraction, X-Ray Fluorescence Spectroscopy, Fourier Transform Infrared Spectroscopy, 27Al NMR-MAS and Field Emission Scanning Electron Microscopy. The obtained results indicate the predominance of Smectite phase in clays due to high swelling capacity and cation exchange observed. The predominance of Smectite phase was confirmed by XRD, XRF and FTIR, which also indicates the presence of quartz and other minerals. Were also evaluated the presence of organic compounds in the interlayer space of modified clays and was noted that have not changes in their crystalline structures, based on FTIR and 27Al NMR-MAS results. The SEM-FEG micrography confirms the irregularity of cluster size, according to expect to bentonite clays. The performed characterizations for these clays minerals determine its elementary composition and makes possible distinguish the four samples according to its place of origin by the amount of impurities, as well as the prevalence of smectite phase. The characterization analysis were used to quantification of fundamental properties and to evaluated the organic compounds presence in interlayer space through of delocalization of the most intense peak in 2θ angle. The obtained results are useful for the benefit of industrial areas such as pharmaceutical, food, environmental and others, once the mineral clays properties can be improved when properly identified and quantized.